IMPACT OF FINANCIAL STRESS ON STUDENTS’ ACADEMIC ACHIEVEMENT - PANKAJ KUMAR (International Journal of Multidisciplinary Research and Studies, 2021)
A person's time spent as a student is sometimes regarded to be the most interesting and eventful of their whole life. This is due to the fact that this period of time is typically packed with memories and experiences that the individual will always cherish. Through engagement in a wide range of recreational, cultural, and academic activities, students get the nourishment they need and are better equipped to handle the responsibilities that come with reaching adulthood. This circumstance, when seen from a more in- depth vantage point, makes it feasible to grasp the challenge that college students encounter in their life on a daily basis. The whole idea of going to college and having.a life that is both joyful and engaging at the same time is riddled with concerns that inevitably result in stress. In the case that they are not addressed, they have the potential to affect the kids' academic performance, as well as their emotional and social well-being. If this occurs, the school should take immediate action. Throughout the course of the last several decades, there has been a dramatic shift in the financial mechanisms that are used to support higher education. This could be the result of a number of factors stemming from a large number of circumstances, such as the combination of economic deprivation and factors such as the expense of school, the curriculum, and the workload